2021
DOI: 10.3390/jof7030178
|View full text |Cite
|
Sign up to set email alerts
|

T2Candida for the Diagnosis and Management of Invasive Candida Infections

Abstract: Invasive candidiasis is a common healthcare-associated infection with high mortality and is difficult to diagnose due to nonspecific symptoms and limitations of culture based diagnostic methods. T2Candida, based on T2 magnetic resonance technology, is FDA approved for the diagnosis of candidemia and can rapidly detect the five most commonly isolated Candida sp. in approximately 5 h directly from whole blood. We discuss the preclinical and clinical studies of T2Candida for the diagnosis of candidemia and review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
(127 reference statements)
0
26
0
Order By: Relevance
“…A recent multicenter study, reported by Monday et al [15], isolated mixed yeast infections in approximately 2% of cultures from sterile sites. The paired reporting of T2MR results (i.e., C. albicans/C.…”
Section: Bodymentioning
confidence: 99%
See 4 more Smart Citations
“…A recent multicenter study, reported by Monday et al [15], isolated mixed yeast infections in approximately 2% of cultures from sterile sites. The paired reporting of T2MR results (i.e., C. albicans/C.…”
Section: Bodymentioning
confidence: 99%
“…T2MR does not provide antifungal susceptibility data but the combination of MAg together with T2MR identified all isolates [11]. It remains unclear how to clinically interpret the approximately 30% of cases that have positive T2Candida with negative BCs [4,6,15]. BCs can detect 1 CFU/mL of most Candida sp.…”
Section: Bodymentioning
confidence: 99%
See 3 more Smart Citations